The stress analysis of thin-walled screwed tubular joints - Broadbent, T.P. (1988)
This report presents the findings of a project studying the stress analysis of screwed tubular joints using photoelastic and finite element techniques. The aim of the work was to optimise the thread form to be used in large diameter, thin walled, tubular screwed joints which may be used as connections in the tethers of Tension-Leg Platforms. Frozen-stress, photoelastic techniques were used to measure the distributions of thread load and peak fillet stresses around the thread spirals of models with different thread shapes and loaded with different loading modes of axial tension, preload only, preload plus tension and eccentric tension. From detailed photoelastic measurements of the distribution of stress around individual thread fillets it was found that the fillet stress at any position in the thread spiral is the sum of those due to the stresses in the model wall plus those due to the shear force carried by the thread. Due to the time and cost involved in manufacturing and analysing a sufficient number of Araldite models to carry out a full analysis of the effect of thread parameters on fillet stresses it was decided to use axisymmetric, 8 noded, isoparametric, finite elements. Fillet stress distributions obtained using finite elements and 3- dimensional photoelasticity were checked for agreement of results for threads of similar shapes before the range of shapes analysed was extended using finite elements. It was found that simple trigonometric functions in terms of the position around the thread fillet accurately described the fillet stress distribution. The effect of changing thread shape on the fillet stresses could also be described by using simple functions of the parameters concerned. Both the trigonometric and parametric functions were different for wall tension and shear force loading, but they could be combined to give the fillet stress distribution in a typical thread loaded with both shear force and wall tension. The accuracy of the equations developed was investigated by comparing the predicted distributions of position and magnitude of peak fillet stresses with those measured in the 3- dimensional Araldite models. The pitch-average peak fillet stresses were generally within +/- 10% of each other. Finally, the effect of altering thread parameters was investigated using the equations developed.